INTERFERENSI FONOLOGIS BAHASA MELAYU PATTANI DALAM BERBAHASA INDONESIA MAHASISWA THAILAND DI UNIVERSITAS MUHAMMADIYAH SURAKARTA - Aseeyah Kuwing (Balai Bahasa Nusa Tenggara Barat, 2017)
The purpose of this study is to describe a form ofphonological interference of Malay Pattani language in Indonesian language of Thai students at the University of Muhammadiyah Surakarta. This type of research is qualitative descriptive. The data source of this research is Thai students at the University of Muhammadiyah Surakarta. Data were collected by listening, recording, and interviewing. Data were analyzed using match method with translational type and contrastive analysis method. There is one thingaddressed in this study; Existence of phonological interference of Malay Pattani language in Indonesian language of Thai students at the University of Muhammadiyah Surakarta. The study shows that (a) Interference phonological elements found in the phoneme replacement, phoneme deletion, substitution of syllables, and syllables deletion. (b) Interference also found in the lexicon of nouns, verbs, adjectives, pronouns, bookmark, adverbs, prepositions and question words. (c)syntaxInterference found in the type of news sentences, interrogative sentence, and imperative sentences.